الإجراءات أمام المحكمة الإدارية في القانون الأردني والمقارن - الحسين محمد; خشمان محمد (Latakia University Journal - Economic and Legal Sciences Series, 2017)
هدفت الدراسة إلى التعرف على الجهد الذي بذله المشرع الأردني في سبيل تطوير القضاء الإداري والتغلب على جميع المعوقات التي تعترض هذا التقدم، خاصة بعد إجراء التعديل الدستوري في الأردن عام 2011م. واعتماد مبدأ التقاضي الإداري على درجتين بإصداره قانون القضاء الإداري رقم 27 لسنة 2014م. والذي يعد خطوة مهمة في بناء دولة مؤسساتية تحترم حقوق الإنسان وتعزز قيم الديمقراطية في المجتمع. كما ناقشت هذه الدراسة، من خلال تحليل نصوص قانون القضاء الإداري الأردني الجديد ومقارنتها بأنظمة القضاء الإداري في مصر، مواطن الضعف والقوة في هذه التعديلات الجديدة التي من شأنها إذا ما أخذ بها المشرع الأردني أن تجعل القضاء الإداري الأردني نظيرا لا يستهان به للقضاء الإداري المصري ولا سيما إن مصر قد قطعت شوطاً كبيراً في هذا المجال يزيد على عدة عقود. لذا تجب الاستفادة من هذه التجربة و تطبيقها على القضاء الأردني. This study aims to high light the effort of the Jordan legislator in order to developed the Administrative Judiciary Law and defeat all the challenges for the advancement of law, especially after the constitutional amendment in Jordan during 2011 .The Law appreciates the principle of administrative trail in Wisata liburan Alternatif di puncak two degrees as issued under Administrative Judicial Law No 27 in 2014. Nevertheless, these initiatives apprehend important steps to build institutional State that respects human rights and promotes democratic values in society. This study analyses critically the new Jordanian Administrative Judicial Law and compares with Egyptian Administrative Judicial Law, in order to pay attention on weakness and strengths of the Jordanian legislation. The critical analysis can help to make the Administrative Judicial Law as unique by following the experience of the Egypt.